RANCANG BANGUN SISTEM INFORMASI EVENT ORGANIZER BERBASIS WEB DI ANTIQUE SALON DAN PELAMINAN - PRATAMA, MUHAMMAD IQBAL; Syastra, Muhammad Taufik (Computer Science and Industrial Engineering, 2021)
Information technology serves to help facilitate human work in all aspects of life. The Infortmation Systems is functioned for the purpose of improving the Event Organizer service. A website - based infortmation systems is needed as a transmitter of informations in increasing customer interest so that they can see details of items and packages in detail. The method of data collection is by a using obserrvation techniques, literrature studies, and interviewss. The systems diesign methode used is the waterfalls where the stagess are plannings, analysise, design, and system testings. Website designs using CodeIgniter4 framework, Bootstrap4, and MySQLto shortens the times with satisffactory result. With the developments of this informations systems, it is hoped that it can be a solutions to the problemss faced at Antique Salon and aisles in conveying detailed information regarding details of items, packages, services offered and other features.